Nutritional Status and Energy Intake of Adolescents in Umuahia Urban, Nigeria - Ogechi, Ukegbu Patricia; Akhakhia, Onimawo Ignatius; Ugwunna, Ukegbu Andrew (Pakistan Journal of Nutrition, 2007)
The purpose of this study was to provide information on anthropometry, body composition and energy intake of adolescents South Eastern Nigeria. The participants were 190 apparently healthy adolescent boys and girls aged 15-18 years with equal sex distribution. Participants were subjected to anthropometric measurements viz: height, weight, arm circumference and skinfold thickness. Energy intake was determined from individual weighed inventory for three consecutive days including a week-end day; part of the food sample was subjected to chemical analysis. According to the results, all measurements except BMI and arm circumference had significant differences (p<0.05). Approximately 50% girls and well over 70% boys failed to meet the recommended weight and height standards. Over 20% of the adolescents were thin (BMI<18.5kg/m2). The prevalence of overweight indicated that about 4% of boys and 2% of girls were at risk of becoming overweight. Similarly the prevalence of stunting was found to be 67.3% and 57.8% for boys and girls, respectively. In addition, body fat percent was significantly higher in girls (p<0.05). The mean intakes for fat, carbohydrate and energy was significantly higher in males compared to females (p<0.05). This research provides information concerning anthropometry, body composition and energy intake of adolescents, South East Nigeria. The result shows that there was under nutrition among the adolescents though the extent was higher among adolescent boys than girls, body composition of the adolescents was equally low. Also protein intake was grossly inadequate in both sexes. Therefore there is a need for improvement in the nutritional status among these adolescents.